2022
DOI: 10.3389/fimmu.2022.1032911
|View full text |Cite
|
Sign up to set email alerts
|

High titre neutralizing antibodies in response to SARS–CoV–2 infection require RBD–specific CD4 T cells that include proliferative memory cells

Abstract: BackgroundLong-term immunity to SARS-CoV-2 infection, including neutralizing antibodies and T cell-mediated immunity, is required in a very large majority of the population in order to reduce ongoing disease burden.MethodsWe have investigated the association between memory CD4 and CD8 T cells and levels of neutralizing antibodies in convalescent COVID-19 subjects.FindingsHigher titres of convalescent neutralizing antibodies were associated with significantly higher levels of RBD-specific CD4 T cells, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 93 publications
2
13
0
Order By: Relevance
“…Unlike CD40L, which is biased toward expression on T-helper type 1 (Th1) cells, OX40 is expressed equally on all Th cells, including Tregs, potentially reducing bias when analyzing antigen-specific T cells. 16,23,24 It is important to note that OX40 is highly expressed on murine FOXP3 + Tregs,…”
Section: Cell Surface Receptors Validated For Aim Assays With Human B...mentioning
confidence: 99%
See 4 more Smart Citations
“…Unlike CD40L, which is biased toward expression on T-helper type 1 (Th1) cells, OX40 is expressed equally on all Th cells, including Tregs, potentially reducing bias when analyzing antigen-specific T cells. 16,23,24 It is important to note that OX40 is highly expressed on murine FOXP3 + Tregs,…”
Section: Cell Surface Receptors Validated For Aim Assays With Human B...mentioning
confidence: 99%
“…101 A study of long-term immunity to SARS-CoV-2 found that increased levels of S receptor-binding domain-specific CD25 + OX40 + CD4 + T cells associated with higher neutralizing antibody titers, with single-cell transcriptomics revealing a heterogenous population. 24 More recently, AIM assays have been used to determine vaccine-induced protection against omicron and other emerging SARS-CoV-2 variants. The CD25/ OX40 assay indicated that individuals receiving ChAdOx-1S, Ad26.COV2.S, mRNA-1273 or BNT162b2 vaccines had no significant differences in the level of antigenspecific T cells when stimulated with ancestral spike protein as compared with delta, beta and omicron variant spike proteins, while antibody levels against omicron were significantly decreased.…”
Section: Detecting Sars-cov-2-specific T Cells Following Infection An...mentioning
confidence: 99%
See 3 more Smart Citations